Antimicrobial activity and mineral composition of shiitake mushrooms cultivated on agricultural waste - Kasuya, Maria Catarina Megumi; Casaril, Kérley Braga Pereira Bento; Vanetti, Maria Cristina Dantas (Brazilian Archives of Biology and Technology, 2011)
The antimicrobial activity and mineral composition of shiitake mushrooms were evaluated in four isolates of Lentinula edodes. Mushrooms were cultivated on artificial logs, based on eucalyptus sawdust enriched with 20% rice, wheat, or soybean bran, or combination of 10% of two of these supplements. The substrates were humidified with a 0.1% mate tea extract or water. Logs of Eucalyptus grandis were also used to cultivate the shiitake mushrooms. The antimicrobial activity of an aqueous extract, corresponding to 40 mg of mushroom dry matter, was in some cases, depending on the isolate, able to inhibit both Bacillus subtilis and Escherichia coli K-12, independent of substrate composition or the growth stage of the mushrooms. Nitrogen, phosphorus, potassium, magnesium and calcium concentrations varied according to the substrate on which the mushrooms were cultivated, being, generally, higher with cultivation on artificial rather than natural eucalyptus logs. It could be concluded that, in addition to the fungal isolate, substrate composition and, processing methods must be considered during the production of antimicrobial substance(s) as well as in the mushroom nutritional composition
Keywords: Antibacterial property; Lentinula edodes; Mineral nutrients; Sawdust-based substrate; Mushrooms